MENGUNGKAP WAWASAN DIMENSI ETIS-TEOLOGIS DAN ETIS-ANTROPOLOGIS DALAM PENGEMBANGAN PONDOK PESANTREN - marfu'ah, siti; Sassi, Komarudin (LPPM UM Metro, 2025)
This study aims to reveal the ethical-theological and ethical-anthropological dimensions in the development of Islamic boarding schools (pondok pesantren) as Islamic educational institutions that play a strategic role in shaping students’ character and promoting social transformation. Using a qualitative-descriptive approach and an interpretive paradigm, this research examines how theological and humanistic values are integrated into the educational system of pondok pesantren and the life of the Muslim community. The findings indicate that the ethical-theological dimension is rooted in the principle of tawhid as the spiritual and moral foundation of all educational activities within the pesantren. Meanwhile, the ethical-anthropological dimension is manifested through social and cultural practices that emphasize respect for humanity, da’wah lil-ummah (preaching for the community), solidarity, and the responsibility of civilizational development. Both dimensions form a model of theocentric-anthropocentric humanism, representing a balanced integration between spirituality and humanity. The pesantren thus functions not only as an institution for transmitting religious knowledge but also as an agent of moral and social transformation relevant to the challenges of modernity. The integration of ilahiyyah values as the ethical-theological dimension and insaniyyah values as the ethical-anthropological dimension positions the pesantren as a model of holistic Islamic education aimed at nurturing God-conscious, knowledgeable, and civilized human beings.